Integration of Economic Analysis of Law and Restorative Justice in Criminal Law Reform: An Interdisciplinary Approach for Efficiency and Humanization of the Justice System - Lesmana, CSA Teddy (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study aims to analyze the challenges of the Indonesian criminal justice system, particularly its lack of effectiveness, efficiency, and substantive justice caused by overcriminalization and prison overcapacity. The purpose is to develop a more efficient and humane sentencing policy by integrating Economic Analysis of Law (EAL) and Restorative Justice (RJ) into a comprehensive policy framework. The research method used is normative juridical with multidisciplinary approaches, combining conceptual, historical, and comparative analysis. The study critically evaluates weaknesses in the conventional sentencing system, examines the substantive provisions of the 2023 Criminal Code (KUHP), and applies cost-benefit analysis within the framework of restorative justice values. The analysis also considers comparative perspectives from other jurisdictions and incorporates insights from law, economics, criminology, and social sciences to ensure a more holistic understanding. The novelty in this research is the formulation of an integrative EAL-RJ model that not only addresses efficiency through economic considerations but also promotes social restoration, participation, and justice for victims and offenders. Unlike existing approaches that separate deterrence from restoration, this model seeks to combine both objectives in a balanced way. It is designed to be flexible and applicable across different types of crimes, including serious offenses, with decision-making based on evidence, proportionality, and societal participation. Based on the research, it can be concluded that the integration of EAL and RJ offers a promising alternative to conventional punitive sentencing. This integrative model can reduce overcapacity in correctional institutions, enhance cost efficiency, and promote reconciliation and social harmony. The study thus contributes to the development of a more contextual, fair, and restorative-oriented Indonesian criminal justice system that is sustainable in the long term.